Local Administration of Antibiotics in Orthopedics and Traumatology - Gramlich, Yves; Schnetz, Matthias; Hoffmann, Reinhard (Zeitschrift für Orthopädie und Unfallchirurgie, 2023)
2022 marks the 50th anniversary of the development of the antibiotic loaded PMMA chain. The loading of bone cements with antibiotics was a major advance in the treatment of musculoskeletal infections and is still a proven standard today. The research and use of novel antibiotic carriers continues to be an important part of research in the context of musculoskeletal infections. The article provides an overview of the various local antibiotics available and their specifics. In addition, current adapted treatment concepts are discussed.
Keywords: antibiotic carrier; PMMA; antibiotic beads; musculoskeletal infection; Periprosthetic joint Infection; PJI; fracture related infection; FRI; local antibiotics